2000
DOI: 10.1007/s004010051195
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Fas and Fas ligand immunoreactivity after compression trauma to rat spinal cord

Abstract: This immunohistochemical study evaluated Fas and Fas ligand (FasL) in the rat nervous system and their changes in the spinal cord subjected to compression. Normal spinal cord showed a low level of Fas and FasL immunoreactivity in the white matter except in the corticospinal tracts. Fas and FasL immunoreactivity seemed to be located in axons and their myelin sheaths. Other regions of the nervous system did not show immunoreactivity to Fas and FasL. Moderate and severe compression injury of the spinal cord resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 30 publications
0
15
1
Order By: Relevance
“…Both DR4 and DR5 are present in the CNS of mammalians (Dörr et al, 2002) and mediate the detrimental effects of TRAIL in brain ischemia (MartinVillalba et al, 1999) and in b-amyloid-dependent neurotoxicity (Cantarella et al, 2003). Although it has been shown that after SCI, expression of TNF, CD95, and CD95L is increased at the lesion site (Zurita et al, 2001;Xu et al, 1998;Li et al, 2000), the in vivo function of the receptors belonging to TNFR superfamily and the respective ligands in SCI is still controversial. Neutralization of TNF (Lee et al, 2000) and CD95L (Demjen et al, 2004) reduces the number of apoptotic cells after SCI.…”
Section: Introductionmentioning
confidence: 99%
“…Both DR4 and DR5 are present in the CNS of mammalians (Dörr et al, 2002) and mediate the detrimental effects of TRAIL in brain ischemia (MartinVillalba et al, 1999) and in b-amyloid-dependent neurotoxicity (Cantarella et al, 2003). Although it has been shown that after SCI, expression of TNF, CD95, and CD95L is increased at the lesion site (Zurita et al, 2001;Xu et al, 1998;Li et al, 2000), the in vivo function of the receptors belonging to TNFR superfamily and the respective ligands in SCI is still controversial. Neutralization of TNF (Lee et al, 2000) and CD95L (Demjen et al, 2004) reduces the number of apoptotic cells after SCI.…”
Section: Introductionmentioning
confidence: 99%
“…The Fas/ Fas ligand system in apoptosis has fundamental roles in the immune system (Nagata, 1997), and current studies have shown the involvement of Fas/Fas ligand signaling in CNS pathophysiology (Beer et al, 2000;Dowling et al, 1996;Li et al, 2000;Nishimura et al, 1995). For example, Fas ligand mRNA expression increased in the cerebral cortex after permanent middle cerebral artery occlusion (MCAO) in adult rats (Harrison et al, 2000), and Fas ligand mRNA and its protein were expressed in the cerebral cortex after reversible MCAO in adult rats (Herdegen et al, 1998;Martin-Villalba et al, 1999;Rosenbaum et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Procaspase-8 is proteolytically cleaved and consequently activates caspase pathways, thereby leading cells to apoptosis. The Fas/Fas ligand system, which was first documented in the immune system (Suda et al, 1993;Yonehara et al, 1989), is also important in CNS pathophysiology, such as Alzheimer disease (Nishimura et al, 1995), multiple sclerosis (Dowling et al, 1996), trauma (Beer et al, 2000;Li et al, 2000), and ischemia (Felderhoff-Mueser et al, 2000;Herdegen et al, 1998;Martin-Villalba et al, 1999;Matsushita et al, 2000;Northington et al, 2001;Rosenbaum et al, 2000;Tarkowski et al, 1999). Recently, it was shown that the Fas/Fas ligand system has a role in the mitochondrial apoptotic pathway by cleaving the Bcl-2 family member Bid (Li et al, 1998;Luo et al, 1998).…”
mentioning
confidence: 99%
“…Thus, it is not implausible that PLA 2 -induced necrotic death of SK-N-SH cells is associated with Fas-mediated death pathway identified in the present study. A number of studies have shown that elevated expression of Fas and FasL is observed in varying neurologic disorders such as infectious, inflammatory, degenerative, infectious, traumatic, neoplastic, developmental, and ischemic disorders [Beer et al, 2000; Ferrer et al, 2000Ferrer et al, , 2001Li et al, 2000], but little is known about the regulation of Fas and FasL expression in neuron cells during injury. Our data suggest a signaling pathway for N. naja atra PLA 2 -induced Fas and FasL upregulation, resulting in necrotic death of human neuroblastoma SK-N-SH cells.…”
Section: Signaling Pathway Of Pla 2 In Inducing Death Of Sk-n-sh Cellsmentioning
confidence: 98%